Psychogenic Nonepileptic Seizures: Evidence from Empirical Research - Carlson, Catherine A (Medical Science: Recent Advances and Applications Vol. 5, 2025)
Psychogenic non-epileptic seizures (PNES) are defined as paroxysmal episodes which clinically resemble epileptic seizures but, unlike the latter, do not show an epileptiform discharge on ictal vEEG electrodes. An estimated 15% to 30% of patients referred to epilepsy-monitoring units for drug-resistant epilepsy walk away with a diagnosis of PNES. Seizures that do not produce an epileptiform discharge on the ictal video electroencephalogram (vEEG) will likely garner the ‘rule in’ diagnosis of PNES, or Conversion Disorder in modern nomenclature. The absence of an epileptiform discharge is considered proof that the seizure is not epileptic and thus, it presumably has a psychological origin. For decades, the scalp EEG has been hailed as the ‘gold standard’ for distinguishing PNES from epilepsy and a great deal of empirical data has been amassed on the PNES patient population. Though the PNES diagnostic entity is treated as a proven fact, in truth, it rests on but one hypothesis that might explain a negative scalp EEG. The purpose of this paper is to review the literature and assess whether the hypothesis that underlies the PNES diagnosis is supported or refuted by the empirical data. Since not all epileptic seizures produce a scalp EEG correlate, an epileptic seizure is a recognised competing hypothesis for a negative scalp finding. Studies that gather data from both scalp and intracranial EEG recordings show that scalp-negative epileptic seizures are not uncommon, but in modern epilepsy-monitoring units, they are at high risk of being mislabeled PNES. Both epilepsy and PNES patient populations show pervasive brain disease, including structural alterations and both are considered network disorders. Both seizure types have remitted or failed to remit on AEDs, and both conditions demonstrate instances of prolonged seizure activity, designated status epilepticus and pseudo-status epilepticus in patients with epilepsy and PNES, respectively. To assess for such diagnostic error, it must turn to the empirical evidence, which shows that the clinical profiles of PNES and epilepsy patient populations are identical. The similarities are striking, and the only data the PNES hypothesis can explain is a negative scalp EEG. Conversely, the competing epileptic hypothesis seamlessly accounts for the bulk of the findings on patients with seizures labelled PNES. The diagnostic terrain is further muddied by the ongoing conflation of conscious feigning with conversion disorder, which represents a long-standing conceptual error. The data establishes that the PNES patient population consists primarily of patients with epilepsy, along with a smattering of factitious and likely psychotic disorders, thereby exposing the PNES diagnostic entity as a hypothetical construct that does not exist. Diagnostic theory and practice in epilepsy-monitoring units must be revisited. Intracranial monitoring, seizure-alert trained dogs, high-density scalp EEG, scalp-negative seizure detectors, and scalp EEG zero-crossing patterns could all provide further proof that the PNES population consists primarily of patients with epilepsy.